Studies of delta operator and its application to a tank level control process - Wen, Zhaopiao. (2008)
In many practical applications, the usual shift operator formulation is inferior to an alternative, called the delta operator. The main objective of this project is to study some numerical advantages of the delta operator, and apply the delta operator to implement a controller for a time delay process.